A flame retardant synergism of organic disulfides and phosphorous compounds. (July 2016) - Wagner, Jochen; Deglmann, Peter; Fuchs, Sabine; Ciesielski, Michael; Fleckenstein, Christoph A.; Döring, Manfred
Abstract: A highly efficient halogen-free flame retardant system for polystyrene foams consisting of phosphororganic compounds and synergists of the general structure RSSR is described here and mechanistic details of its mode of action are given. Compared to the corresponding individual components, the flame retarding effect is enhanced or actually imparted by the use of various combinations of those compounds. Among the disulfides investigated bis(benzothiazolyl)disulfide showed the best synergistic effect. Bis(diphenylphosphinothiolyl)disulfide as a one-component flame retardant combining phosphorous entities and a disulfide bridge in one molecule exhibits a similar flame retardant efficiency. Polystyrene samples containing these additives were analyzed by thermal desorption mass spectrometry (TD-MS), whereby the release of S2 -fragments during the thermal decomposition of the disulfides could be detected even in the case of systems for which a cleavage of SS bonds would rather be expected. Based on these experiments and extensive quantum chemical calculations a conclusive mechanism is derived, which can help to design future flame retardant additives.